Structural Measures against Tsunamis - Ishiwatari, Mikio; Sagara, Junko (World Bank, Washington, DC, 2013)
Structures such as dikes play a crucial role in preventing disasters by controlling tsunamis, floods, debris flows, landslides, and other natural phenomena. However, structural measures alone cannot prevent all disasters because they cannot mitigate damages when the hazard exceeds the level that the structures are designed to withstand. The Great East Japan Earthquake (GEJE) demonstrated the limitations of Japan's existing disaster management systems, which relied too heavily on dikes and other structures. Damage can be kept to a minimum by multilayered approaches to disaster mitigation that include structural and nonstructural measures and that ensure the safe evacuation of residents. This report gives findings; lessons; and recommendations for developing countries.